A Syntactic Analysis of the Sentence Structure in Motivational Quotes using Tree Diagram for English Learning - Diah Ayu Kristianingsih; Akhmad Haqiqi Ma’mun; Zuhad Ahmad (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
Syntax is a branch of linguistics that explains sentence structure. This study aims to discover what types of sentences are used in motivational quotes, which frequently emerge in motivational quotes, and describe sentence structure utilizing a tree diagram. This research employs the descriptive qualitative technique. The study involved multiple processes in data collection, including; reading the novel's text, choosing sentences of motivational quotes contained in the novel Atomic Habits, and writing down all the sentences of motivational quotes selected for analysis. The data were analyzed using Noam Chomsky’s theory “Transformational Generative Grammar”. The result of the study shows that the motivational quotes from the novel Atomic Habits have all types of sentences. In addition, the researcher also found the types of sentences that frequently emerge in motivational quotes from the novel, namely 22 simple sentences, 2 compound sentences, five complex sentences, and one compound-complex sentence. So, the dominant motivational quote is a simple sentence. This study has various types of sentences in motivational quotes that can be used to help English learners and improve writing skills in a text or essay according to grammatical rules.